1979
DOI: 10.1002/jcp.1040980317
|View full text |Cite
|
Sign up to set email alerts
|

Growth of human embryonic fibroblasts at clonal density: Concordance with results from mass cultures

Abstract: In the past, it has been difficult to grow human diploid fibroblast cells at clonal densities. Newly devised cell culture media and rigorously controlled environmental conditions have greatly increased the ease with which such cells can be cloned. The present work was undertaken to determine whether, under appropriate conditions, diploid fibroblast cells from human embryonic lung, grow as well at clonal densities as in mass culture. The parameters studied were: (1) population doubling time, (2) in vitro prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The end of the replicative lifespan was defined by failure of the population to double after 4 weeks in mass cultures. The in vitro lifespan (remaining replicative capacity) was expressed as population doubling (PD) up to cellular senescence (25). The population doublings were calculated with the equation PD ϭ log 10 (N/N 0 ) ϫ 3.33, where N is the number of cells at the end of the experiment and N 0 is the number of cells at the beginning of the experiment (26).…”
Section: Methodsmentioning
confidence: 99%
“…The end of the replicative lifespan was defined by failure of the population to double after 4 weeks in mass cultures. The in vitro lifespan (remaining replicative capacity) was expressed as population doubling (PD) up to cellular senescence (25). The population doublings were calculated with the equation PD ϭ log 10 (N/N 0 ) ϫ 3.33, where N is the number of cells at the end of the experiment and N 0 is the number of cells at the beginning of the experiment (26).…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro lifespan (remaining replicative capacity) was expressed as population doublings up to cellular senescence. 5,26 Telomerase assay Presenescent osteoblasts from donors, transfected with either the hTERT cDNA-expressing plasmid or control plasmid, were treated with ice-cold hypotonic detergent lysis buffer (10 6 cells/100 ml: 0.5% CHAPS (Sigma)), incubated on ice for 30 min, and centrifuged at 12 000 g for 20 min at 41C. The supernatant was stored at À801C.…”
Section: Determination Of the Lifespan Of Human Osteoblastic Cellsmentioning
confidence: 99%
“…If cultures were continuously kept in a logarithmic growth state, there was initially enhanced proliferation activity. 53,54 This is explainable by population genetic tools. If telomeric length polymorphism at each chromosome end in a fibroblast culture is considered as an analogue to the allele frequencies at a single gene locus in a natural population of individuals, one can use the concept of genetic drift.…”
Section: Correlations Of Culture Sizes and Cumulative Population Doubmentioning
confidence: 95%
“…2,3,7,9,26,38,44,45 As shown for a great number of different fibroblast strains, there is a progressive increase in replicatively senescent cells until the culture cannot be propagated further. 2,[4][5][6][7][8][9][10][11][12][13][14][15]46,47 It has been repeatedly demonstrated that the onset of that terminal state is clearly related to the replicative age, that is, to mitotic time, of the culture and not to chronological time, [48][49][50][51] and that cell proliferation capacities are not adversely affected by growth at low cell density [52][53][54] nor by enzymatic treatment at passaging. 55 Therefore, the consumption of an intrinsically determined proliferation capacity by divisions represents the final replicative boundary which human fibroblasts cannot continuously bypass.…”
Section: Introductionmentioning
confidence: 99%